Application Development for Fasting and Worship Management Ramadan Using the Incremental Method: Kareem - Daffa Fakhir; Nabila Al Buqari Jufri; Muh Akhlatul Ihsan; Putri Nirmala; Ummul Khaeri Masna (Sakura Digital Nusantara, 2025)
The development of Artificial Intelligence (AI) in education, especially in design teaching, offers great potential to improve students' creativity, reflection, and design thinking mindset. This study aims to evaluate the effect of AI integration in design-based learning on students' creative thinking ability, reflection, and design mindset. The study used quantitative methods with a cross-sectional design, involving 82 respondents from various departments in higher education institutions. The research instrument was a questionnaire covering aspects of creativity, reflection, and design mindset. The data analysis technique used descriptive analysis. The results showed that 59.76% of the respondents were 19 years old, and most (85.37%) were 3rd semester students. The use of AI in design-based learning was proven to increase student creativity with an average score of 3.66 on a scale of 5, strengthen reflection skills with an average of 3.63, and improve design thinking mindset with an average of 3.75. However, the results also revealed that AI is more effective as a supporting tool in the learning process rather than replacing direct interaction between students and educators. Therefore, AI can be integrated as a tool that supports creativity, but still requires the role of human guidance.